The glymphatic system in Huntington's disease - Duan, Wenzhen; Zhou, Yuan; Liu, Hongshuai (Journal of Huntington's disease, 2025)
The glymphatic system, a macroscopic waste clearance network in the brain, plays a vital role in maintaining neuronal health and brain homeostasis. Functionally analogous to the lymphatic system in other organs, the term "glymphatic" combines "glial" and "lymphatic." This system facilitates the exchange of cerebrospinal fluid (CSF) and interstitial fluid (ISF) in the parenchyma, aiding in the removal of soluble proteins and metabolites while distributing essential nutrients and signaling molecules. Its functionality is closely tied to aquaporin 4 (AQP4) water channels, located primarily on astrocytic endfeet, which mediate water movement between the CSF and ISF. Proper glymphatic function relies on the cellular distribution of AQP4 channels and its astroglial endfeet polarization. Emerging evidence links glymphatic dysfunction to several neurodegenerative disorders, including Huntington's disease (HD). Understanding the role of the glymphatic system in HD pathogenesis could provide novel insights into disease pathogenesis and new therapeutic approaches. This review examines the connection between glymphatic dysfunction and HD, highlighting future research directions and therapeutic advancement for HD. It explores pharmacological interventions and lifestyle modifications aimed at optimizing glymphatic function to improve HD management.